Estudo da influência da cultura organizacional nas questões ambientais da indústria metalúrgica - Nunes, Marcos Tadeu Marcondes (2022)
Metallurgy was one of the first industrial processes developed by humanity, being improved according to the evolution of this species. Before, practically artisanal, today extremely industrialized and technologically updated. Inherently, its nature is a polluting industry, and can reach abiotic environments such as soil, air and water, thus impacting the balance of different food chains. The controls of its environmental impacts are mandatory and the results observed by a demanding market. Investments go beyond technological modernization, as it is verified that attention to human beings is essential in the development of an organizational culture that is conscious and committed to good environmental performance, thus naturally guaranteeing better results in performance indicators, and when associated with planning strategy, better competitive conditions in the market. Methodology: This study aims to understand from a Systematic Literature Review (SLR): i) how are the debates about the influence of organizational culture on environmental issues; ii) understand how organizational culture influences an Environmental Management System (EMS); and iii) whether the involvement of senior management is relevant in aspects related to organizational culture. The research shows an urgent need to produce knowledge in this area. Therefore, in view of this conclusion, pointing to the aridity of technical-scientific productions, which could more effectively guide this sector, the effective contribution of this dissertation is to indicate an area to be better explored and studied.